The Impact of a Pulmonary-Artery-Catheter-Based Protocol on Fluid and Catecholamine Administration in Early Sepsis - Carina Bethlehem; Frouwke M. Groenwold; Hanneke Buter; W. Peter Kingma; Michael A. Kuiper; Fellery de Lange; Paul Elbers; Henk Groen; Eric N. van Roon; E. Christiaan Boerma (Critical Care Research and Practice)
Objective. The pulmonary artery catheter (PAC) remains topic of debate. Despite abundant data, it is of note that many trials did not incorporate a treatment protocol. Methods. We retrospectively evaluated fluid balances and catecholamine doses in septic patients after the introduction of a PAC-based treatment protocol in comparison to historic controls. Results. 2×70 patients were included. The first day the PAC group had a significantly higher positive fluid balance in comparison to controls (6.1±2.6 versus 3.8±2.4 litre, 𝑃<0.001). After 7 days the cumulative fluid balance in the PAC group was significantly lower than in controls (9.4±7.4 versus 13±7.6 litre, 𝑃=0.001). Maximum dose of norepinephrine was significantly higher in the PAC group. Compared to controls this was associated with a significant reduction in ventilator and ICU days. Conclusions. Introduction of a PAC-based treatment protocol in sepsis changed the administration of fluid and vasopressors significantly.